USE AND EFFICACY OF AI PLATFORMS FOR CONTENT CREATION TO INFLUENCE TRAVEL THROUGH SOCIAL MEDIA - Chawla, Sayani; Sood, Ritu S; Chawla, Amit (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Introduction: In this paper, the main aim of the research is to know the use of AI platforms in content creation for travel in social media. The aim and objectives along with the research question that are met in this research paper are stated below. Literature review: The studies that inspired the purpose and objectives of this research paper are stated under the Literature Review. The “social media interference warfare theory” and “cyberspace model” has been discussed mitigating the challenge those are faced in AI content creation. Methodology: Primary quantitative research method has been followed with a survey questionnaire. From 103 total population, post filtering the non AI platform users, 60 people as the sample size was finalized with random sampling technique. The participants responded to 10 questions and the data were analyzed with regression analysis through IBM-SPSS as software. Findings and discussion: Data has been analyzed with the help of SPSS tool. Correlation, and frequency with ANOVA have been analyzed and the results have been compared with the literature review. Similarity has been found and a correlation among the variables has been noticed. Conclusion: It has been concluded that the use of AI in content creation for travel and influencing people with social media is useful. The factors post credibility, user intention and trust and loyalty positively impact the travellers, where social media as a content creation tool is found effective.